Pendugaan Zona Alterasi Hidrotermal Menggunakan Data Geomagnetik EMM 2017 Di Wilayah Lubuk Sikaping - Fauzan Surya Nanda; Arif Budiman (Jurnal Fisika Unand, 2025)
This study aims to identify hydrothermal alteration zones in Lubuk Sikaping District, Pasaman Regency, West Sumatra, using Enhanced Magnetic Model (EMM) 2017 geomagnetic data developed by the National Oceanic and Atmospheric Administration (NOAA). The data processing stages include International Geomagnetic Referee Field (IGRF) correction, evaluation of regional and residual anomalies using Radial Average Power Spectrum (RAPS), reduction to the poles, analysis of magnetic anomaly values ​​with the geological conditions of the study area. The results show that residual magnetic anomalies are in the range of -7.09582 nT to 7.65333 nT. The results of the analysis of magnetic anomaly values ​​and geological conditions indicate that the high anomaly zone (3.12460 nT - 7.65333 nT) spread in the south and southwest is a mineralization zone. The moderate anomaly zone (0.07503 nT - 3.12460) spread in the central to northeast is a lithology preservation zone between magnetic igneous rocks and non-magnetic sedimentary rocks. The low anomaly zone (–7.09582 nT - 0.07503 nT) located in the north and northeast is a hydrothermal alteration zone. The presence of mineralization zones, lithology boundary zones and hydrothermal alteration zones indicates that there is a fluid migration path in this area. The hydrothermal alteration zone in Lubuk Sikaping District is associated with the Sarik-Gajah Formation which consists of volcanic rocks that have undergone alteration due to the presence of active structures of the Sumatran Fault System.